Biomechanical evaluation of locked plating fixation for unstable femoral neck fractures. Issue 6 (June 2020) - Bliven, E.; Sandriesser, S.; Augat, P.; von Rüden, C.; Hackl, S.
Abstract : Aims: Evaluate if treating an unstable femoral neck fracture with a locking plate and spring-loaded telescoping screw system would improve construct stability compared to gold standard treatment methods. Methods: A 31B2 Pauwels' type III osteotomy with additional posterior wedge was cut into 30 fresh-frozen femur cadavers implanted with either: three cannulated screws in an inverted triangle configuration (CS), a sliding hip screw and anti-rotation screw (SHS), or a locking plate system with spring-loaded telescoping screws (LP). Dynamic cyclic compressive testing representative of walking with increasing weight-bearing was applied until failure was observed. Loss of fracture reduction was recorded using a high-resolution optical motion tracking system. Results: LP constructs demonstrated the highest mean values for initial stiffness and failure load. LP and SHS constructs survived on mean over 50% more cycles and to loads 450 N higher than CS. During the early stages of cyclic loading, mean varus collapse of the femoral head was 0.5° (SD 0.8°) for LP, 0.7° (SD 0.7°) for SHS, and 1.9° (SD 2.3°) for CS (p = 0.071). At 30, 000 cycles (1, 050 N) mean femoral neck shortening was 1.8 mm (SD 1.9) for LP, 2.0 mm (SD 0.9) for SHS, and 3.2 mm (SD 2.5) for CS (p = 0.262). Mean leg shortening at construct failure was 4.9 mm (SD 2.7) for LP, 8.9 mm (SD 3.2) for SHS, and 7.0 mm (SD 4.3) for CS (p = 0.046). Conclusion: Use of the LP system provided similar (hip screw) or better (cannulated screws) biomechanical performance as the current gold standard methods suggesting that the LP system could be a promising alternative for the treatment of unstable fractures of the femoral neck. Cite this article: Bone Joint Res 2020;9(6):314–321.